The complete mitochondrial genome of Triplophysa nanpanjiangensis Zhu and Cao 1988 (Cypriniformes: Nemacheilidae) - Jingzhuang Zhao; Li Zou; Lu Tian; Mingqiu Liu; Haibo Jiang; Zhonggui Xie; Zhiqiang Liang (Mitochondrial DNA. Part B. Resources, 2023)
AbstractThe genus Triplophysa is an ideal taxon for understanding geological evolution. In this study, for the first time, we report the complete mitochondrial genome of T. nanpanjiangensis Zhu and Cao 1988 using the Nanopore sequencing. It is a circular genome with a length of 16558 bp, comprising 22 tRNAs, 13 protein-coding genes (PCGs), two rRNAs, and one non-coding control region. The phylogenetic tree demonstrates that T. nanpanjiangensis is sister to Triplophysa zhenfengensis and placed within the genus Triplophysa. Our mitogenomic studies provide a new pathway for understanding the molecular phylogeny of the genus Triplophysa.